The Capel Wetlands Centre: A survey of its Historical Development, Significance and Research Results - Davies, Stephen (2002)
The Capel Wetlands Centre was established in 1985 when a sandmining company resolved to rehabilitate large pits at Capel as an environment for waterbirds instead of as pine plantation and pasture. The Royal Australasian Ornithologists Union was commissioned to manage the rehabilitation and instituted a research programme that aimed to identify management options leading to the development of a self-sustaining ecosystem at the site. Hydrology, water quality, biological resources and rehabilitation techniques were examined. As the Capel Wetlands Centre matured it became a focus for school and university projects and a regional recreational resource within the Living Windows Ecomuseum system. This bulletin summarises the history of the site, the results of the research programme and the potential of the Capel Wetlands Centre as a link in the conservation estate of south-westem Australia.